2022
DOI: 10.1007/s00701-022-05453-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-respondents do not bias outcome assessment after cervical spine surgery: a multicenter observational study from the Norwegian registry for spine surgery (NORspine)

Abstract: Background The Norwegian registry for spine surgery (NORspine) is a national clinical quality registry which has recorded more than 10,000 operations for degenerative conditions of the cervical spine since 2012. Registries are large observational cohorts, at risk for attrition bias. We therefore aimed to examine whether clinical outcomes differed between respondents and non-respondents to standardized questionnaire-based 12-month follow-up. Methods All ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…However, a NORspine study showed no difference in outcomes between responders and non-responders [33]. We found no difference in RTW ratios between responders and non-responders in our study, which is consistent with previous studies indicating that non-responders do not bias evaluation of PROMs [7,14,15]. Even so, we do not know the exact reasons for non-respondence, and our results must be interpreted with this in mind.…”
Section: Limitationssupporting
confidence: 81%
“…However, a NORspine study showed no difference in outcomes between responders and non-responders [33]. We found no difference in RTW ratios between responders and non-responders in our study, which is consistent with previous studies indicating that non-responders do not bias evaluation of PROMs [7,14,15]. Even so, we do not know the exact reasons for non-respondence, and our results must be interpreted with this in mind.…”
Section: Limitationssupporting
confidence: 81%
“…Previous reports from the Norwegian and Danish spine registries have found that data are missing at random, and outcomes after cervical and lumbar spine surgery are similar between respondents and nonrespondents. [62][63][64] Moreover, we found similar results in the complete case analyses and mixed-model analyses. Therefore, we do not consider that loss to follow-up introduced any attrition bias in this study.…”
Section: Limitationssupporting
confidence: 81%
“…Loss to follow-up is a concern, but previous NORspine studies on degenerative lumbar and cervical spine surgery have shown no differences in outcomes between responders and nonresponders. 28,29…”
Section: Discussionmentioning
confidence: 99%
“…Loss to follow-up is a concern, but previous NORspine studies on degenerative lumbar and cervical spine surgery have shown no differences in outcomes between responders and nonresponders. 28,29 Because of the high proportion of patients with mild myelopathy and short duration of symptoms in our study, the generalizability of the results across other patient populations with more severe and chronic long-term preoperative symptoms is a concern. Our study is, however, a cohort from a national registry and represents consecutive patients from everyday practice.…”
Section: Figure Global Perceived Effectmentioning
confidence: 99%